Bibliometric Review on Digital Economy and Industry Convergence: The Impact of Digitalization on Business Adaptation and Innovation - Loso Judijanto; Yusniar Yusniar; Rosyid Nurrohman; Eko Sudarmanto; Endang Supriatna (Westscience Press, 2024)
This study presents a bibliometric analysis of research on digital economy and industry convergence, with a focus on the impact of digitalization on business adaptation and innovation. Using data from key databases, including Scopus and Web of Science, and visualized through VOSviewer, the analysis reveals key themes, influential authors, and evolving research trends from 2000 to 2024. The findings highlight that